A clinical study of peroral endoscopic myotomy reveals that impaired lower esophageal sphincter relaxation in achalasia is not only defined by high-resolution manometry. - Hiroki Sato; Kazuya Takahashi; Ken-Ichi Mizuno; Satoru Hashimoto; Junji Yokoyama; Shuji Terai (PLoS ONE, 2018)
Achalasia is an esophageal motility disorder characterized by impaired lower esophageal sphincter (LES) relaxation. On high-resolution manometry (HRM), impaired LES relaxation is defined by elevated integrated relaxation pressure (IRP). However, a new category of achalasia within the normal IRP range has been suggested.HRM was performed using a Starlet device and an IRP threshold of 26 mmHg. Peroral endoscopic myotomy (POEM) was performed for cases of achalasia diagnosed using established methods. During POEM, the histology of the LES was assessed. Follow-up was performed 2 months post-operatively.Forty-one patients with achalasia (18 women, mean age 53 ± 18.6 years) were included. Among them, 27 were placed in the IRP > 26 mmHg subgroup (impaired LES relaxation on HRM) and 14 in the IRP ≤ 26 mmHg subgroup (normal LES relaxation on HRM). In the IRP ≤ 26 mmHg subgroup, patients were older, had longer symptom duration, and had more esophageal dilation. The IRP ≤ 26 mmHg subgroup had the same symptom severity as the higher IRP subgroup and POEM significantly improved symptoms and IRP, although four patients still had severe LES fibrosis.The clinical presentation of achalasia has a gap between a HRM-defined impaired LES relaxation, with aging or disease progression considered reasons for a lowered LES pressure. POEM can be a feasible treatment option, even for cases of achalasia with a normal IRP. However, patients with severe LES fibrosis need more attention for the therapeutic indication.